THE ANGIOTENSIN CONVERTING ENZYME-INHIBITORY EFFECTS OF THE PEPTIDE ISOLEUCINE-TRYPTOPHAN AFTER ORAL INTAKE VIA WHEY HYDROLYSATE IN MEN. (June 2018) - Martin, M.; Hagemann, D.; Henle, T.; Deussen, A.
Abstract : Objective: Angiotensin-Converting Enzyme (ACE)-inhibitors are treatment of choice in hypertensive patients. In former studies we revealed the ACE-inhibitory activity and antihypertensive effect of the natural dipeptide isoleucine-tryptophan (IW) and its effect on cardiac remodelling and coronary flow reserve in spontaneously hypertensive rats. The aim in this project was to determine in volunteers the ACE-inhibiting effect and the bioavailability of IW after oral intake of whey hydrolysate. A second aim was to study the influence of combined intake of IW-containing hydrolysate with further food ingredients. Design and method: 8 fasted normotensive volunteers received IW containing whey hydrolysate in different doses, intact whey protein, or water. Compounds were applied alone or with parallel intake of specific food ingredients (fiber, protein, carbohydrates and fat). Blood samples were taken at fixed time points for analysis of ACE activity and assessment of IW concentration in plasma by LC-MS/MS method. Results: Baseline concentrations of IW differed individually ranging from 1.2 to 2.1 nM. The intake of 10 g hydrolysate (equivalent to 50 mg IW) induced a significant increase in plasma IW concentrations (maximum values 8.5–27.5 nM after 25–30 min). The activity of plasma ACE was significantly reduced to 72 – 87% of baseline activity during this time interval. The maximum of ACE inhibition coincided with the peak of IW concentration. Increasing the applied hydrolysate to 50 g caused IW concentrations to increase to 18–159 nM after 29–65 min. In parallel, ACE activity was decreased to 62–77%. However, after intake of intact whey protein IW concentrations increased only slightly to 2.3–4.9 nM and ACE activity was 88–91% of baseline activity. No changes in IW concentration and ACE activities were observed following placebo application. Combined intake of either protein, fiber or fat delayed IW resorption and extended IW rise of plasma concentration and ACE inhibition. Carbohydrates did not affect IW resorption, however, ACE inhibition was diminished compared to the single application of hydrolysate. Conclusions: In healthy volunteers oral intake of IW via whey hydrolysate shows a marked increase of IW plasma concentration and inhibition of plasma ACE activity. In addition, effects are retarded by parallel intake of food ingredients.